The feel-good effect at mega sport events: recommendations for public and private administration informed by the experience of the FIFA World Cup 2006 - Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2008)
One of the most important social effects of the 2006 football World Cup was the feel-good effect. The present contribution is one of the first to deal with the development of a general theory for the management of feel-good effects and systematically analyses the influencing factors taking the 2006 World Cup as an example. Of importance are suitable basic organizational and infrastructure conditions in the realms of security, transport, and ecology. The media activities of public and private sponsors should break away from the traditional narrow focus and classic brand sponsoring in favor of a more socially responsible sponsoring. Sporting success of the home team is important, which may be due in equal measures to the style of play of the team and its demeanor. The creation of generally accessible participation opportunities through free TV in the host country and the setting up of fan festivals can counteract any frustration that might arise from the allocation of ad-mission tickets. Any targeted manipulation of the weather may be considered with due regard to possible ecological implications.
Keywords: H83; L83; M14; 330; Feel-good Effect; Sports Economics; World Cup; Mega-Events; Image Effects; Public Viewing